The COVID-19 pandemic, well-being, and transitions to post-secondary education - Malte Sandner; Alexander Patzina; Silke Anger; Sarah Bernhard; Hans Dietrich (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2021)
This study examines the immediate and intermediate effects of the COVID-19 pandemic on the well-being of two high school graduation cohorts (2020 and 2021). We also investigate how changes in well-being at the transition to post-secondary education affect educational plans and outcomes. Our unique panel data contain prospective survey information on three dimensions of well-being: mental health problems, self-rated health, and life satisfaction for 3,697 students. Data is collected several months before (fall 2019), shortly before and soon after (spring 2020), and several months after (fall/winter 2020/21) the outbreak of the COVID-19 pandemic. Applying difference-in-differences designs, random effect growth curve models, and linear regression models, we find that school closures had a positive immediate effect on students' well-being. Over the course of the pandemic, however, well-being strongly declined, mainly concentrated among the 2021 graduation cohort. Finally, we show that a strong decline in mental health is associated with changes in educational and career plans and transition outcomes. As adverse life experiences in adolescence are likely to accumulate over the life course, this study is the first to exhibit potential long-lasting negative effects of the COVID-19 pandemic on education and careers of young individuals. – – Wir untersuchen den Zusammenhang zwischen der Covid-19-Pandemie und dem Wohlbefinden von Abiturienten und Abiturientinnen. Über den Verlauf der Covid-19-Pandemie verschlechterte sich das Wohlbefinden der jungen Erwachsenen deutlich. Insbesondere die starke Verschlechterung der psychischen Gesundheit geht mit veränderten (Aus-)Bildungsentscheidungen und Karriereplänen einher. Damit zeigen wir hier erstmalig die nachhaltigen, negativen Effekte der Covid-19-Pandemie auf die Bildungsentscheidungen und Karrierepläne junger Menschen.
Keywords: I21; I18; J24; 330; COVID-19; High school graduates; Mental and physical well-being; Life satisfaction; School-to-work transition